Improvement Trends for Internal Combustion Engines 2018
DOI: 10.5772/intechopen.69740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Waste Cooking Oil Biodiesel Blends on Performance and Emissions from a CRDI Diesel Engine

Abstract: The employment of biofuels in blends with diesel oil proved to attain a reduced environmental impact without compromising the engine performance. Among biofuels, waste cooking oil offers the advantages of its reduced raw material cost in comparison with fresh vegetable oil cost; it also eliminates the environmental impacts caused by its disposal. Although a great number of researches has been devoted to biodiesel combustion in engines and pollutant emissions, few studies can be found on light duty diesel engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Based on the results obtained in this study, as well as the results of other authors, can be concluded that engine performances and exhaust emissions of diesel engine depend not only on the type of fuel but also on the engine technical characteristics such as compression ratio [26], fuel injection system [22], ignition type [12,16], injection pressure [30], as well as the engine operating mode (load and speed).…”
Section: Exhaust Gases Analysissupporting
confidence: 65%
See 3 more Smart Citations
“…Based on the results obtained in this study, as well as the results of other authors, can be concluded that engine performances and exhaust emissions of diesel engine depend not only on the type of fuel but also on the engine technical characteristics such as compression ratio [26], fuel injection system [22], ignition type [12,16], injection pressure [30], as well as the engine operating mode (load and speed).…”
Section: Exhaust Gases Analysissupporting
confidence: 65%
“…The lowest torque values at all measurement points and significantly lower (P˂0.05) average engine torque were achieved using a B20 blend, while between other fuels there were no significant differences (P˂0.05) in engine torque. Chiatti et al [22] showed the variation of engine torque with speed at fullload condition for diesel fuel and blends with 20% and 40% WCO and concluded that the torque trend at fullload condition depends on the proportion of WCO in the fuel; since WCO has a lowering heating value than diesel fuel. With that are agree [20], with additional opinion that high engine torque with pure diesel is due to the fact that the density of WCO blend is higher than that of the pure diesel fuel, therefore a larger mass flow at low engine speeds engine torque increases with the higher proportion of WCO, while at high engine speeds the modified operation of a mechanical governor is observed and the governor starts to reduce injected fuel quantity earlier when the higher proportion of WCO is used and engine torque decrease faster.…”
Section: Diesel Engine Performancesmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of waste oil biodiesel in com pression ignition engines results in im proved emission characteristics with th e exception of NOx and CO2. [41][42][43].…”
Section: Waste Oil Biodieselmentioning
confidence: 99%